Beyond Adoption: Understanding the Consumer Impact of Digital Marketing in Emerging Economies Through a Systematic Review - Mukhtar Galib; Johannes Baptista Halik (Journal of Marketing Management and Innovative Business Review, 2026)
Digital marketing adoption has expanded rapidly across emerging economies, creating new opportunities for firms to influence consumer behavior. However, evidence regarding its impact on long-term consumer outcomes remains fragmented and theoretically inconsistent. This study aims to synthesize the existing literature on digital marketing adoption and consumer behavior in emerging economies while identifying key mechanisms that shape the conversion of digital engagement into sustainable consumer value. A systematic literature review (SLR) was conducted following the PRISMA 2020 guidelines, resulting in a final sample of 47 substantive studies published between 2015 and 2025. The findings indicate that digital marketing adoption is driven by technological, social, and institutional factors, including perceived usefulness, social influence, trust, digital literacy, and infrastructural readiness. While digital marketing consistently enhances consumer engagement and purchase intention, its effects on loyalty, advocacy, and long-term commitment remain inconsistent across contexts. This review identifies a persistent conversion gap between consumer engagement and sustainable consumer outcomes, highlighting limitations in adoption-centric theories such as TAM and UTAUT. To address this gap, the study proposes an Institutional Conversion Framework that integrates technological, relational, and institutional dimensions to explain post-adoption consumer behavior. The study contributes to theory development and offers practical insights for digital marketers, platform providers, and policymakers in emerging economies.